Local-Regional Therapy Response in Hepatocellular Carcinoma: A Clinical Evaluation - Navaneetha Kumar Govarthanan; Meyyappan M; Biji Babu; Dirisala Anudeep; Anita S (Asian Journal of Medical Sciences, 2026)
Background: Accurate assessment of treatment response after locoregional therapy is essential in hepatocellular carcinoma (HCC). European Association for the Study of Liver (EASL), modified response evaluation criteria in solid tumors (mRECIST), and liver imaging and reporting data system (LI-RADS) treatment response (LI-RADS TR) are widely used imaging-based criteria with potential differences in response categorization. Aims and Objectives: The aim of the study is to evaluate the treatment response of HCC following locoregional therapies using EASL, mRECIST, and LI-RADS TR criteria and to assess the concordance between EASL and the other response assessment systems. Materials and Methods: This retrospective analytical study included 40 patients with HCC who underwent locoregional therapy. Pre- and post-treatment multiphasic computed tomography/magnetic resonance imaging examinations were evaluated using EASL, mRECIST, and LI-RADS TR criteria. Concordance between EASL and the other response assessment systems was assessed using cross-tabulation and Chi-square analysis. Results: The mean age was 61.59±9.79 years, and 80.0% of patients were male. Transarterial chemoembolization (TACE) was the most common treatment modality (55.0%). Using EASL, complete response, partial response (PR), stable disease, and progressive disease were observed in 45.0%, 7.5%, 35.0%, and 12.5% of patients, respectively. By mRECIST, complete response and PR were observed in 45.0% and 20.0% of patients. LI-RADS TR classified 50.0% of lesions as non-viable, 32.5% as viable, and 17.5% as equivocal. Significant concordance was observed between EASL and mRECIST and between EASL and LI-RADS TR (P